Case Report: Complete pathological remission of human chorionic gonadotrophin-producing gallbladder carcinoma with multiple liver metastases after treatment with chemotherapy plus an immune checkpoint inhibitor - Wang, Qianwen; Mu, Yunchuan; Ji, Shunxian; Liu, Yang; Lou, Yanbo; Wei, Shumei; Dong, Xin; Zhang, Bo (Frontiers in Immunology, 2023)
Background: Gallbladder carcinoma (GBC) producing human chorionic gonadotrophin (HCG) is an extremely rare and highly invasive tumor, with a poor prognosis. This unfavorable clinical outcome is partly due to its aggressive nature and insensitivity to chemotherapy. Case Presentation: We herein reported a case of primary GBC producing HCG with liver metastases in a 58-year-old female. The patient presented with markedly elevated β-HCG level and a mass in gallbladder with multiple liver metastasis. A definitive diagnosis was obtained after needle biopsy of liver metastases, showing poorly differentiated carcinoma with large-scale necrosis and strong positivity of immunostaining for HCG in tumor cells. The patient received chemotherapy (gemcitabine plus capecitabine) combined with immune checkpoint inhibitor (ICIs, carrellizumab). Pathological complete response was achieved after 8 courses of combined therapy, which was confirmed by pathological analysis of resected specimens. After surgery, 2 courses of chemotherapy plus ICIs were adopted again. Complete response remained for approximate 1 year up to present. Tumor tissue was collected to perform immunostaining of PD-L1, whole-exome sequencing and RNA-seq. Low-TMB (1.51 mut/Mb), MSS and high PD-L1 expression (TPS ≥ 50%) were observed in the tumor. Besides, the dominant types of infiltrating immune cell were macrophage and CD4+ T cell. Compared to other gallbladder adenocarcinoma without HCG, the proportion of M1 macrophage was in higher level and the gene sets of MYC targets v1 and PI3K/AKT/mTOR signaling were highly expressed in our case. To our knowledge, this is the first case report of complete remission of HCG-producing gallbladder carcinoma with liver metastasis after chemotherapy combined with ICIs. Furthermore, this is also the first report that described the tumor genetic feature and tumor immune microenvironment atlas of HCG-producing GBC. Conclusions: Chemotherapy plus immune checkpoint inhibitor may provide a potential curative option for gallbladder carcinoma with HCG producing.